Egrang An Analytical Study of the Traditional Game Egrang and Its Impact on Physical Fitness - Maretno (Athena: Physical Education and Sports Journal, 2026)
This study aims to determine the impact of implementing the traditional sport egrang on students’ learning outcomes in physical fitness material within Physical Education, Sports, and Health (PJOK) learning. This research is motivated by the low motivation and learning outcomes in PJOK, which are caused by conventional teaching methods and the lack of engaging learning media variations. The study seeks to improve PJOK learning outcomes in the cognitive, affective, and psychomotor domains through the integration of the traditional egrang sport. The method used is Classroom Action Research (CAR), conducted in two cycles consisting of planning, implementation, observation, and reflection stages. The research subjects were 10 tenth-grade students. Data were collected through learning outcome tests and student activity observation sheets, which were then analyzed using descriptive quantitative and qualitative methods. The results showed that in Cycle I, students’ learning outcomes were in the sufficient category, with several obstacles related to movement coordination and understanding of the rules. However, after improvements were made in Cycle II, there was a significant increase, with learning outcomes reaching the good category. Students demonstrated improvements in basic movement skills (psychomotor), understanding of game strategies (cognitive), and the reinforcement of sportsmanship and cooperation values (affective). The conclusion of this study is that the implementation of the traditional egrang sport is effective in improving the quality of the learning process and PJOK learning outcomes of tenth-grade students through contextual learning based on local wisdom.